Role of Burnout in Relationship between Belonging and Resilience In Traumatized Individuals - AYDOĞDU, BİLGE NURAN; EKŞİ, HALİL (My University, 2022)
Individuals encounter at least one negative experience or traumatic event in their lifetime and react differently to these experiences. While some develop vulnerability in the face of such events, others grow stronger. Psychological resilience is the individual’s ability to display healthy development despite negative experiences or to positively adapt to challenging situations. Risk factors and protective factors play an important role in the development of resilience. Therefore, the current study aimed to investigate the effect of burnout as a risk factor and the sense of belonging as a protective factor in explaining psychological resilience. Particularly, this study mainly investigated the mediating role of burnout in the relationship between the sense of belongingness and psychological resilience among university students who had experienced at least one traumatic event. The age of the participants varied between 17 and 35 (M = 24.17, SD = 3.90). General Belongingness Scale, the Resilience Scale for Adults (RSA), and the Burnout Measure, Short Version were used as data collection tools. In data analysis, Pearson Product Moment Correlation and Structural Equation Modeling were performed. It was found that the fit indices established in the research provided good fits and the obtained coefficients were statistically significant. The theoretical model confirmed that burnout plays an intermediary role and significantly affects the relationship between the general sense of belongingness and psychological resilience.

Bireyler yaşamları boyunca en az bir olumsuz deneyim ya da travmatik bir olayla karşılaşır ve bu deneyimlere farklı şekillerde tepki verirler. Bazı bireyler bu yaşanılanlar karşısında kırılganlık geliştirirken, diğerleri daha da güçlenirler. Psikolojik dayanıklılık, bireyin karşılaştığı olumsuz deneyimlere rağmen sağlıklı bir gelişim gösterebilmesi veya riskli durumlar karşısında iyi uyum sağlayabilmesidir. Dayanıklılığın gelişmesinde risk faktörleri ve koruyucu faktörler önemli rol oynamaktadır. Bu nedenle tükenmişlik ve aidiyet duygusunun psikolojik dayanıklılığa etkisinin araştırılması amaçlanmıştır. Bu temelden hareketle, bu çalışmada öncelikle en az bir travmatik olay yaşayan ve yaşları 17 ila 35 arasında değişen üniversite öğrencilerinin aidiyet duygusu ile psikolojik dayanıklılıkları arasındaki ilişkide tükenmişliğin aracı rolü araştırılmıştır (M = 24.17, SD = 3.90). Bu araştırmada veri toplama aracı olarak Genel Aidiyet Ölçeği, Yetişkinler İçin Dayanıklılık Ölçeği (RSA) ve Tükenmişlik Ölçeği Kısa Versiyonu kullanılmıştır. Veri analizinde Pearson Momentler Çarpımı Korelasyonu ve Yapısal Eşitlik Modellemesi kullanılmıştır. Araştırmada oluşturulan uyum indekslerinin iyi uyum sağladığı ve elde edilen katsayıların istatistiksel olarak anlamlı olduğu bulunmuştur. Teorik model, tükenmişliğin aracı bir rol oynadığını ve genel aidiyet duygusu ile psikolojik dayanıklılık arasındaki ilişkiyi önemli ölçüde etkilediğini doğrulamaktadır.
Keywords: travma; psikolojik sağlamlık; aidiyet; tükenmişlik; yol analizi; trauma; psychological resilience; sense of belonging; burnout; path analysis